Electrodeposition of Silver Vanadate Films: A Tale of Two Polymorphs. Issue 20 (16th September 2019) - Vali, Abbas; Sarker, Hori P.; Jee, Hyung‐Woo; Kormányos, Attila; Firouzan, Farinaz; Myung, Noseung; Paeng, Ki‐Jung; Huda, Muhammad N.; Janáky, Csaba; Rajeshwar, Krishnan
Abstract: Two polymorphs of AgVO3, namely the α‐ and β‐ forms, were prepared and their physical, structural, optical, electrochemical, and photoelectrochemical characteristics were compared using a battery of experimental and theoretical tools. A two‐step method, previously developed in the our laboratory for the electrodeposition of inorganic semiconductor films, was applied to the electrosynthesis of silver vanadate (AgVO3 ) films on transparent, conducting oxide surfaces. In the first step, silver was cathodically deposited from a non‐aqueous bath containing silver nitrate. In the second step, the silver film was anodically stripped in an aqueous medium containing ammonium metavanadate. The anodically generated silver ions at the interface underwent a precipitation reaction with the vanadate species to generate the desired product in situ. Each of these steps were mechanistically corroborated via the use of electrochemical quartz crystal microgravimetry, used in conjunction with voltammetry and coulometry. As‐deposited films were crystalline and showed p‐type semiconductor behavior. Theoretical insights are provided for the electronic origin of the α→β phase transformation in AgVO3 and the disparate optical band gaps of the two polymorphs. Finally, implications for the application of this material in solar cells are provided. Abstract : Two sides of the same coin : Theoretical and experimental results are presented for two polymorphs of silver vanadate. This semiconductor material was electrodeposited via a two‐step approach pioneered in our laboratory. Electronic band structures, structural and optical data, and photoelectrochemical behavior for the two polymorphs are compared. Perspectives for solar photovoltaic applications are finally offered.